Pre-service Physical Education Teachers’ Occupational Socialisation through the Field Experience: 敎育學院體育師訓生於學校敎學實習職化過程的探討 - LI, Chung (Asian Journal of Physical Education & Recreation, 2002)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. This paper is concerned with a qualitative study of how three pre-service physical education teachers who were comparatively less skilful in sports, socialised professionally in their first field experience. It was a part of the two-year study project investigating the occupational socialisation of pre-service physical education teachers in the Hong Kong Institute of Education. With the interpretive paradigm as the conceptual framework, data concerning the professional conceptions, socialising strategies and perceptions on their socialising agents during their first field experience were collected through interviewing and writing of reflective journals. The findings demonstrated a particular socialisation process of this type of recruits. Interestingly, they were found shaping their early belief from "being liked by the pupils" to "being proficient in sports skills and instructional competence" as important requirements for PE teaching after the first field experience. The wash out effect of the field experience on the physical education teacher education programme was particular significant on them. The findings provide information about how a particular group of recruits socialised professionally in their first field experience. In return, such implications can be facilitated positively in teacher education. 此研究目的是利用詮釋理念，透過會談及反思報吿以搜集資料，探討三位運動技能水平較同班學員稍遜之敎育學院體育及運動科學系學生之第一次學校敎學實習的經歷，藉以瞭解他們的職化過程。在整個敎學實習中，他們由初期只深信「取悦學生」之敎學手法，逐漸轉化至明白「運動技能水平」及「敎學能力」對體育敎師敎學的重要性。研究結果有助加深了解這類準體育敎師的社化過程及敎學實習經驗的效果。